2022
DOI: 10.1088/1758-5090/ac84b1
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional human adipocyte model of fatty acid-induced obesity

Abstract: Obesity prevalence has reached pandemic proportions, leaving individuals at high risk for the development of diseases such as cancer and type 2 diabetes. In obesity, to accommodate excess lipid storage, adipocytes become hypertrophic, which is associated with an increased pro-inflammatory cytokine secretion and dysfunction of metabolic processes such as insulin signaling and lipolysis. Targeting adipocyte dysfunction is an important strategy to prevent the development of obesity-associated disease. However, it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It was demonstrated that the adipocytes presented with larger lipid droplets and metabolic profiles compatible with hypertrophy, such as increased basal lipolysis and insulin resistance. Thus it proves to be a valuable tool in the studies of adipocyte dysfunctions because of obesity [ 116 ].…”
Section: Alternative Methods To Animal Testing In Adipogenesismentioning
confidence: 99%
“…It was demonstrated that the adipocytes presented with larger lipid droplets and metabolic profiles compatible with hypertrophy, such as increased basal lipolysis and insulin resistance. Thus it proves to be a valuable tool in the studies of adipocyte dysfunctions because of obesity [ 116 ].…”
Section: Alternative Methods To Animal Testing In Adipogenesismentioning
confidence: 99%
“…Recently, Pieters and collaborators (2022) treated human ASC embedded into hydrogel with fatty acids after adipogenic differentiation. The resulting adipocytes showed obese characteristics such as hypertrophy, increased lipolysis, and insulin resistance [ 103 ]. The phenomenon of lipolysis is commonly described in fat depots with more inflammatory properties, such as VAT [ 104 ].…”
Section: Adipose Tissue 3d Modelsmentioning
confidence: 99%
“…In the past 10 years, several new models of adipose tissue have been developed with varying degrees of complexity [ 11 ]. Many of these models support the 3D environment through the use of scaffolds, such as silk [ 12 , 13 ], Matrigel [ 14 ] or Geltrex [ 15 ], collagen [ 16 ], and fibrinogen [ 17 ]. More recently, efforts have been made to increase the complexity of adipose models by including other cell lineages that are found in native adipose tissue.…”
Section: Introductionmentioning
confidence: 99%